2017
DOI: 10.1103/physrevb.95.054304
|View full text |Cite
|
Sign up to set email alerts
|

Glassy dynamics in CuMn thin-film multilayers

Abstract: Thin film multilayered spin glass CuMn/Cu structures display glassy dynamics. The freezing temperature, T f , was measured for forty layers of CuMn films of thickness L = 4.5, 9.0, and 20.0 nm, sandwiched between non-magnetic Cu layers of thickness ≈ 60 nm. The Kenning effect, T f ∝ ℓn L, is shown to follow from power law dynamics where the correlation length grows from nucleation as ξ(t, T ) = c1a0(t/τ0) c 2 (T /Tg ) , leading to [(T f /Tg)c2ℓn(tco/τ0)] + ℓnc1 = ℓn(L/a0). Here, Tg is the bulk spin glass tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 47 publications
9
33
0
Order By: Relevance
“…For a polycrystalline bulk thiospinel, Joh et al found at a reduced temperature of T /T c = 0.72, z c = 7.576. There is no way of knowing the crystallite size in these "bulk" measurements, but they were certainly larger than the thin film thicknesses of Zhai et al [7]. Zhai et al found, for CuMn 11.7 at.% thin films at reduced temperatures of T /T c = 0.43, 0.59, 0.78, z c = 9.62.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For a polycrystalline bulk thiospinel, Joh et al found at a reduced temperature of T /T c = 0.72, z c = 7.576. There is no way of knowing the crystallite size in these "bulk" measurements, but they were certainly larger than the thin film thicknesses of Zhai et al [7]. Zhai et al found, for CuMn 11.7 at.% thin films at reduced temperatures of T /T c = 0.43, 0.59, 0.78, z c = 9.62.…”
Section: Introductionmentioning
confidence: 85%
“…For x 1, z c grows with ξ, but it is T -independent [9]. Furthermore, a mild extrapolation from z c (ξ = 12 a 0 ) to z c (ξ = 38 a 0 ) [9] is compatible with the thin-film value z c = 9.62 [7] (the film width was ∼ 38 a 0 ). For x 1, the ξ-independent z c (T = T c ) = 6.69±0.06 [9] agrees with the CuMn result at T = 0.95T c , z c = 6.80 [8].…”
Section: Introductionmentioning
confidence: 91%
“…The introduction of a protocol different from conventional measurements of M ZFC (t, T ) is a consequence of the time dependence of the field cooled magnetization, M FC (t, T ), for mesoscale CuMn films. Whereas in bulk, M F C (t, T ) varies little, and if anything, slightly diminishes with increasing measurement time 23 , at mesoscale, it increases rather substantially with increasing measurement time 17 . We believe this is a consequence of glassy dynamics.…”
Section: Sample Preparation and Experimental Protocolmentioning
confidence: 99%
“…The sample preparation and experimental protocol will be described in Section III. The latter will be different from that used in our previous investigation 6,17 , because the field-cooled magnetization in CuMn thin films is time dependent, as noted in previous work 18 , complicating the extraction of the irreversible magnetization. The experimental results will be presented in Section IV, and their analysis in Section V. Section VI contains the summary and conclusions, and Section VII the acknowledgments.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation